Pasangan Perkawinan Dengan Izin Orang Tua Untuk Membentuk Keluarga Sakinah (Studi Kasus Di Kecamatan Penawangan Kabupaten Grobogan Tahun 2010 - 2012) - Hadjar, Ibnu; , Dr. Drs. Imron Rosyadi, M.Ag; , M. Muhtarom, SH.MH (2015)
Marriage under 21 years old in Penawangan sub district Grobogan regency Central Java is social phenomenon which growing on the society. Problems of them influence by factors of their own inhabitants such as economy, education, culture, emotional instability and parental influence. They don't prevent someone to get married because marriage in any age will be influenced by the same factors. Therefore, inhabitants prefer to choose make their child get married rather than continue their study. The result of this research shows sakinah family to the young couple under 21 years old in 2010, 2011 and 2012 in Penawangan sub district Grobogan regency categorized as sakinah family. In their opinion, sakinah family is live in harmony between wife and husband then birth of child and the marriage should be according to syara' (religion) and rules of the country. So, sakinahfamily is they who can implement religion rules and religion guidance and make social-religion interaction with their society. Family is tools to fulfill their belief, God-fearing, good characters needs as social and psychological and regeneration. Therefore, in general marriage under 21 years old is able to build sakinah family. In conclusion, marriage basically is religious orders, moreover Islam recommend it and abhor his followers to stay single (does not want to get marriage), even prophet Muhammad SAW do not consider them as his follower. Someone who wants to get married should be considered aspects such as sexuality, biology, economic and education with expectation to be sakinah family in the future. Basically, the aim of marriage is to build family which is full of sense of love and affection, so the couple will get tranquility. In holy Qur'anit called the concept of sakinah, mawaddah, warahmah, in Ar-Ruum/30:21. Key words: Age, Marriage, Parental Permission, Sakinah